Volatile Constituents of the Flower, Leaf and Stem of Lathyrus vernus (L.) Grown in Turkey - Yilmaz Iskender, Nagihan; Yayli, Nuran; Yasar, Ahmet; Coskuncelebi, Kamil; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
The essential oils obtained from the flower, leaf and stem of Lathyrus vernus (L.) Bernh have been studied. Total 52 compounds were identified, constituting over 97.3, 95.3 and 98.0 % of whole oil composition, respectively. Carboxylic acids were shown to be the main constituents of the flower and stem part in the ratio of 34.2 and 35.3 %, respectively. But, the major components in the leaf oil were found to be alcohols (59.3 %).The main compounds identified in the essential oil of the flower, leaf and stem of L. vernus were palmitic acid (34.2-35.3 %) and 1-octen- 3-ol (49.8 %), respectively.